Kinematic Characteristics of Spermatozoa in Different Goat Breeds Using Computer Assisted Semen Analysis (CASA) - Hanifi, Hirzi; Umar, Sayed; Handarini, Ristika; Maulana, Tulus (Jurnal Agripet, 2025)
Advances in semen quality analysis technology are developing rapidly. Computer-based semen analysis technology provides a more objective assessment of spermatozoa motility by measuring various kinematic movements of spermatozoa cells. This study aimed to analyze differences in spermatozoa movement patterns using Computer-Assisted Semen Analysis (CASA) in various goat breeds. This study used frozen semen from four goat breeds: Boer, Ettawa crossbred (PE), Saanen, and Anglo-Nubian. Parameter observations were conducted on thawed frozen semen from two straw samples for each group, consisting of six replicates from each breed. The observed sperm kinetic movement characteristics were VAP, VCL, VSL, DAP, DCL, DSL, STR, LIN, WOB, ALH, and BCF. The results showed that sperm movements did not differ significantly (P0.05) in VAP, VCL, VSL, DAP, DCL, and WOB. There were significant differences in DSL, the highest in Saanen 21.993.01 m/second, the highest STR and LIN values in Boer 0.690.04% and 0.450.03%, the longest ALH Anglo Nubian 6.190.39 m, and the largest BCF Boer 25.561.87 Hz. This study concludes that differences in goat breeds affect the kinematic movement of spermatozoa as measured by CASA in the parameters of DSL, STR, LIN, ALH, and BCF.